Pelatihan IT Untuk Tenaga Pendidik dan Tenaga Kependidikan UPTD SMP Negeri 3 Towuti, Kec. Towuti, Kab. Luwu Timur, Prov. Sulawesi Selatan - Saman, Saman (Journal of Community Service and Society Empowerment, 2024)
Information technology training was carried out at UPTD SMP Negeri 3 Towuti, Towuti sub-district, East Luwu district, South Sulawesi province. The training was carried out for two days, namely from Friday to Saturday, precisely on 27 - 28 October 2023. The implementation of this activity was carried out using the DIA method. This method was chosen because it is considered quite effective in a teaching and learning process, considering that the participants in this activity are people who are adults in terms of reasoning, thinking and acting. DIA is an abbreviation for Delivery, Interaction, Assessment. Based on the activity evaluation, the results showed that 100% of the 24 teaching staff gained knowledge, 100% of the teaching staff thought that IT training was very useful and they hoped that the training would continue at another time.